IOC consensus statement on training the elite child athlete (2005)
Having identified "Training the Elite Child Athlete" as a theme to be carefully studied, the IOC Medical Commission (MC) last week held a meeting in Lausanne. Coordinated by Margo Mountjoy M.D, member of the IOC MC and Lyle Micheli M.D., of the Harvard Medical School, discussions involved a group of experts including leading paediatric sports medicine and scientific experts from around the world as well as a retired elite child athlete. During the meeting, relative scientific literature was reviewed and safe guidelines were produced for the training of the elite child athlete. At the end of its two-day meeting, the group of experts adopted a consensus (see below). This unique document provides information on the principles of training the child athlete, the identification of overtraining, as well as specific training recommendations. The purpose of this document is to improve the health and safety of the elite child athlete through the promotion of safe training principles and increase awareness among all the persons in his/her entourage. "Protecting the health of the athlete is the primary goal of the International Olympic Committee`s Medical Commission. One of its main objectives is the promotion of safe practices in the training of the elite child athlete. The elite child athlete is one who has superior athletic talent, undergoes specialised training, receives expert coaching and is exposed to early competition. Sport provides a positive environment that may enhance the physical growth and psychological development of children. This unique athlete population has distinct social, emotional and physical needs which vary depending on the athlete`s particular stage of maturation. The elite child athlete requires appropriate training, coaching and competition that ensure a safe and healthy athletic career and promote future well-being. This document reviews the scientific basis of sports training in the child, the special challenges and unique features of training elite children and provides recommendations to parents, coaches, health care providers, sports governing bodies and significant other parties."